Towards advanced regenerative therapeutics to tackle cardio-cerebrovascular diseases - Xi Chen; Weiping Lin; Micky Daniel Tortorella (American Heart Journal Plus)
The development of vascularized organoids as novel modelling tools of the human cardio-cerebrovascular system for preclinical research has become an essential platform for studying human vascularized tissues/organs for development of personalized therapeutics during recent decades. Organ-on-chip technology is promising for investigating physiological in vitro responses in drug screening development and advanced disease models. Vascularized tissue/organ-on-a-chip benefits every step of drug discovery pipeline as a screening tool with close human genome relevance to investigate human systems biology. Simultaneously, cardio-cerebrovascular-on-chip-integrated microfluidic system serves as an alternative to preclinical animal research for studying (patho-)physiological processes of human blood vessels during embryonic development and cardio-cerebrovascular disease. Integrated with next-generation techniques, such as three-dimensional bioprinting of both cells and matrix, may enable vascularized organoid-on-chip-based novel drug development as personalized therapeutics.